Amorphous and anisotropic surface relief formation in tungsten under repeated high-flux hydrogen plasma loads - Yu Li; Junhua Hou; Varun Shah; Yuhe Huang; Johannes A.W. van Dommelen; Wenjun Lu; Qiang Zhu; Thomas W. Morgan (Nuclear Materials and Energy, 2023)
Facing extreme plasma loads, the structural integrity of the tungsten divertor is crucial for ITER, an engineering marvel in nuclear fusion reactors, to achieve its fusion performance targets. Induced by repeated transient heating from plasmas, the thermal fatigue damage of tungsten–typically accompanied by the formation of surface relief–has been identified as a critical issue but an in-depth understanding is still lacking. Here, we report the formation of amorphous and anisotropic surface relief on ITER-grade tungsten surfaces under ITER-relevant hydrogen plasma loads. Measured by both electron backscatter diffraction over large fields of view and transmission Kikuchi diffraction of site-specific lamellae, such surface relief preferentially forms on grains with {110} planes parallel to the surface. This cannot be explained by the orientation-dependent resolved shear stress according to the Schmid law, threshold displacement energy anisotropy, or oxidation anisotropy. Furthermore, surface relief amorphization is revealed by high-resolution transmission electron microscopy imaging and selected area electron diffraction analysis, and is explained by a novel vacancy-induced amorphization mechanism. The results provide new insights into the thermal fatigue behavior of tungsten for fusion applications.